Experimental Characterization and Correlation of Mayer Waves in Retinal Vessel Diameter and Arterial Blood Pressure - Rieger, Steffen; Klee, Sascha; Baumgarten, Daniel (Frontiers in Physiology, 2018)
Retinal vessels show various biological temporal variations, that can impact diagnosis using a static vessel analysis. In this study, Mayer waves in the retinal vessel diameter and arterial blood pressure signals were characterized, and the temporal correlation between these two modalities was investigated. The arterial and venous vessel diameters and arterial blood pressure were recorded simultaneously. The obtained vessel diameters showed vasomotion amplitudes over time. The vessel diameter and blood pressure signals contained multiple signals in the frequency domain and varied over time. The signal characteristics were similar within the measurements. The blood pressure and arterial and venous vessel diameters were correlated. The highest correlation values between the signals were observed for shifts of one or zero periods. The spectrum and amplitudes of the Mayer waves showed a high variability. The Mayer waves in the retinal vessel diameters showed the same characteristics as those in the arterial blood pressure. A temporal dependency between the oscillations in the arterial blood pressure and retinal vessel diameters was shown.